The Impact of Transformational Leadership and Work Motivation on the Performance of Outsourced Employees at PT Citra Insani Garda Semesta - Fathullah Hanung Yasenosa; Zulkifli Rangkuti; Nurwulan Kusuma Devi (Dinasti International Journal of Digital Business Management, 2026)
The purpose of this study was compiled to answer the formulation of the problems that have been determined, namely To analyze the influence of transformational leadership on the performance of outsourcing employees, To analyze the influence of work motivation on the performance of outsourcing employees. To analyze the influence of transformational leadership and work motivation simultaneously on the performance of outsourcing employees at PT Citra Insani Garda Semesta . Transformational leadership has a significant influence on the performance of outsourcing employees. The results of the partial test (t-test) show that the calculated t value of 4.568 is greater than the t table of 1.992 , so the hypothesis is accepted, Work motivation has a significant effect on the performance of outsourcing employees. The results of the partial test show that the calculated t value of 4.308 is greater than the t table of 1.994. Transformational leadership and work motivation simultaneously have a significant influence on the performance of outsourcing employees. Based on the results of the simultaneous test (F test), the calculated F value was 63.643 , which was greater than the F table of 2.73 with a significance level of 0.000 < 0.05 . This indicates that transformational leadership and work motivation together have a significant influence on the performance of outsourcing employees at PT Citra Insani Garda Semesta